Outcome of severe head injury in school age patients at emergency department of hospital universiti sians malaysia - Ismael, Haidi Abdulsalam (2011)
Emergency department Hospital Universiti Sains Malaysia is a referral center for neurosurgical cases for vast area in Kelantan. Head injury patients are referred for neurosurgical intervention and management. Head injury severity, initial vital signs and metabolic response of the patient will affect the overall outcome. The aim of this study is to determine the survival probability of school aged patient with severe head injury treated in Emergency department of HUSM, to determine the mean length of stay (days) of school aged patient with severe head injury treated in Emergency department of HUSM, to determine the prognostic factors that influence the risk of death among school aged patient with severe head injury treated in Emergency department of HUSM and to determine the associated factors that affect the length of hospital stay among school aged patient with severe head injury treated in Emergency department of HUSM. A retrospective chohort study done for a sample of 91 (severe head injury) school aged patients data were collected from the records of HUSM during the period 2007 to 2OO9.These patients were then followed for 30 days following admission to identify their outcome. The mean age was 15.More than 50% of the cases came with initial GCS 6 and above and 67 patients (73.6%) were alive at the end of 30-days.From this study we found that survival probability for severely head injured school aged children was 73.6%. The mean length of stay (days) in hospital was 17 days. Age, CT Finding and GCS of patient at admission were identified as factors related to mortality outcome and to total length of stay in hospital.